Understanding Extension-Library Partnerships: Results from a Three-State Survey - Noah Lenstra; Gary Deziel (Journal of Human Sciences and Extension)
When attending to community needs, collaboration across community organizations yields outcomes that are dynamic and sustaining. Given the interest in collaboration across organizations, and the desire to understand how these partnerships occur, this study sought to explore the collaborative efforts of Extension and public libraries in three states: Kentucky, North Carolina, and Vermont. Foundational information was gathered regarding programming within this partnership, alignment of efforts, and the experiences of partnering from the perspectives of both Extension and library staff, including successes and challenges. Most considered collaboration an expansion to their reach and determined that results included enhanced engagement through cooperation, sharing of resources, coordination, and integration. Ultimately, collaborations such as those seen with Extension and library personnel produce noteworthy impacts on the community.